2022
DOI: 10.1039/d1nr07445h
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity of individual bioelectrocatalytic viral nanoparticles: dependence of catalysis on the viral scaffold and its length

Abstract: The enzymatic activity of tobacco mosaic virus (TMV) nanorod particles decorated with an integrated electro-catalytic system, comprising the quinoprotein glucose-dehydrogenase (PQQ-GDH) enzyme and ferrocenylated PEG chains as redox mediators, is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…The experimental details of cyclic voltammetry (CV) and AFM-SECM experiments have been reported before. ,, The AFM-SECM probes (tips), acting as combined microelectrodes and force sensors, were home-prepared from gold wires of 60 μm diameter as detailed previously . These probes had a spring constant on the order of 1–5 nN/nm and a typical tip radius of ∼100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental details of cyclic voltammetry (CV) and AFM-SECM experiments have been reported before. ,, The AFM-SECM probes (tips), acting as combined microelectrodes and force sensors, were home-prepared from gold wires of 60 μm diameter as detailed previously . These probes had a spring constant on the order of 1–5 nN/nm and a typical tip radius of ∼100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[87][88][89] In addition, the CP-AFM technique has been combined with scanning electrochemical microscopy to investigate the redox-immunomarked proteins 90 and enzymatic activity of individual biocatalytic viral nanoparticles. 91,92 However, the CP-AFM technique has an inherent limitation in that the atomically sharp character of the AFM probe tip is lost after depositing the metal layer by a vacuum evaporation method, and thus the number of proteins in the protein junctions is usually larger than one. A viable strategy to fabricate the single-protein junctions is to combine the CP-AFM technique with the break junctions technique, known as CP-AFM-BJ, which was proposed by Tao et al 93 in 2003.…”
Section: Scanning Probe Microscopy-based Bioelectronic Devicesmentioning
confidence: 99%
“…TMV particles manifest as hollow cylinders with 300 nm in length, and external and internal diameters of 18 and 4 nm, respectively. 81 The well-ordered functional amino acids on the exterior surface of TMV scaffolds endow with patterned immobilization of catalysts/enzymes, facilitating applications in biosensors, 66 online monitoring, and treatment. 50,82 2.2 Dynamic capsid pores and molecular selectivity Numerous studies have revealed the dynamic nature of viral structures, existing as ensembles of various states.…”
Section: Physicochemical Properties Of Viral Capsids and Construction...mentioning
confidence: 99%